Seawater carbonate chemistry and morphology and nutrient physiology of the cosmopolitan marine diatom Thalassiosira rotula - Shea N Wyatt; Brandon J McNabb; Diana E Varela (PANGAEA, 2025)
We investigated the effect of decreased pH on the morphology and nutrient physiology of the cosmopolitan marine diatom Thalassiosira rotula (CCMP3362) by acclimating unialgal cultures to two different CO2 gas concentrations under optimal light, temperature and nutrient conditions. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from UVic Research Data Collection (see Source) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-01-08.